Development of method for quantitative analysis of corn silk for inclusion in the draft national monograph of the State Pharmacopoeia of Ukraine - Karpiuk, Uliana; Kotova, Elina; Kotov, Andriyi; Kyslychenko, Victoriya Victoriya (ScienceRise: Pharmaceutical Science, 2017)
According to the concept of the development and implementation of monographs on herbal material to the State Pharmacopoeia of Ukraine, Corn silk is included into the list of herbal material which is described in the State Pharmacopoeia of the USSR of the XI edition and is absent in the European Pharmacopoeia; therefore, the development of a national monograph on this herb is relevant. Previously it was reported that there are no methods for quantitative determination of biologically active compounds of the given herb in the State Pharmacopoeia of the USSR of the XI edition. Aim. Development of the methods for quantitative determination of flavonoids in Corn silk by absorption spectroscopy, harmonized with the State Pharmacopoeia of Ukraine requirements for herbal material to be implemented into the draft national monograph “Corn silk”. Methods. Unified methods for analysis of flavonoids by absorption spectroscopy were used. Results. Concerning chemical composition, medicinal use and approaches to standardization, flavonoids were selected for identification by spectrophotometry method. Results of the quantitative determination of flavonoids in 7 samples of Corn silk using absorption spectroscopy method are displayed. Conclusion. The necessity of improvement of the existing normative documentation on Corn silk that would meet modern requirements and harmonized with the European Pharmacopoeia was substantiated. In result of the study, it was suggested to implement the method for quantitative determination of flavonoids, calculated as luteolin, with regulation of not less than 0.6 %, into the State Pharmacopoeia of Ukraine national monograph “Corn silk”